2018
DOI: 10.1097/jom.0000000000001220
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in the Workplace

Abstract: Objective To conduct a comprehensive literature review to develop recommendations for managing obesity among workers to improve health outcomes and to explore the impact of obesity on health costs to determine if a case can be made for surgical interventions and insurance coverage. Methods We searched PubMed from 2011–2016, and CINAHL, Scopus, and Cochrane Registry of Clinical Trials for interventions addressing obesity in the workplace. Results A total of 1,419 articles were screened, resulting in 275 art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 109 publications
1
23
0
Order By: Relevance
“…Interestingly, the company decided to introduce the program since it was ―the right thing to do.‖ 40 A business case for providing bariatric surgery coverage for employees could be further argued, since an association has been shown between bariatric surgery and a decrease in lost workdays. 41…”
Section: Attempts To Promote High-value Care and Its Application To Bmentioning
confidence: 99%
“…Interestingly, the company decided to introduce the program since it was ―the right thing to do.‖ 40 A business case for providing bariatric surgery coverage for employees could be further argued, since an association has been shown between bariatric surgery and a decrease in lost workdays. 41…”
Section: Attempts To Promote High-value Care and Its Application To Bmentioning
confidence: 99%
“…Bariatric surgery has proven to be an effective long-term treatment in the control of obesity and associated comorbidities [13,30]. Previous studies [11,16,19,31] have reported improved work performance and employability of patients undergoing bariatric surgery, demonstrating a positive correlation between weight loss and improved work productivity regardless of the professional field, as well as a reduction in direct and indirect costs for the companies [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Some companies have made efforts to implement programs that encourage their workers to take better care of themselves and their weight. This translates into improved efficiency and workplace integration [11].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity adversely affects workplace productivity [31]. Persons with obesity were more likely to be absent from their workplace and less productive while at work due to health-related conditions associated with obesity [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…Participation in a lifestyle intervention which included increased physical activity was reported to enhance workplace productivity by improving physical and mental health in the obese [34]. With these health benefits, absenteeism due to sickness decreases and enhances the ability to work better [31].…”
Section: Discussionmentioning
confidence: 99%